Ethane bridged hybrid mesoporous silsesquioxanes with sulfonic acid functionalities: synthesis, characterization and catalytic applications - Shylesh, S.; Samuel, Prinson P.; Parischa, Renu; Singh, A. P. (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
Periodic mesoporous organosilicas having -CH(2)-CH(2)- groups in the framewall positions and sulfonic acid groups in the pore channels were prepared using 1,2-bis(triethoxysilyl) ethane, 3-mercaptopropyltriethoxysilane and cetyltrimethylammonium surfactant, under basic conditions, by a one-pot synthesis method. XRD, N(2) sorption isotherm and TEM analysis revealed that the mesoporous structural ordering is retained after the functionalization of organic groups while solid-state NMR techniques like (13)C CP MAS NMR and (29)Si MAS NMR show the presence of sulfonic acid groups and the stability of the mesoporous framework with integrated ethane moieties as bridging groups. The hybrid material was more active, selective and stable than the conventional sulfonic acid containing mesoporous catalysts in the Claisen-Schmidt condensation of acetophenone with benzaldehyde to form chalcone.